Penanganan nipple discharge di RS Onkologi Surabaya - DJATMIKO, ARIO; RISTANTO, WIWIEN; ALI, ISKANDAR (Indonesian Journal of Cancer, 2010)
Nipple secretion in nonlactating period often creates anxiety. Frequently this was the reason women came to hospital to be examined. Not all nipple secretion can be defined as nipple discharge. The terminology of nipple discharge is spontaneous fluid secretion from single duct in the nipple in nonlactating women. Generally, nipple discharge is related to non cancerous cause. Yet, many researchers stated that nipple discharge is a sign of breast malignancy. Therefore, accurate diagnostic is vital to differentiate the normal and abnormal nipple discharge. In final analysis, there must be a correct procedure to decide whether nipple discharge is to be operated or not. From January 2007 to December 2009, 10,033 new patients came to Surabaya Oncology Hospital with breast complaints. It turned out 950 cases (9,47%) were malignant. Out of 10,033 patients, 510 (5.08%) complained of nipple secretion. From 510 nipple secretions, 62 were nipple discharge (0.62%). Following the indication, 15 out of 62 cases were operated duct exploration with result 10 were malignant and 5 were benign. From the 15 cases which were operated and preceded by ultrasonography (USG), duct dilatation can be seen. From 10 nipple discharge with malignancy, 7 cases (70%) did not display any Ca suspicion in their mammography examination. Malignancy cases were found more in older age: 7 cases (70%) were above 50 years old. From these 10 cases with malignancy, only 1 case clinically had palpable mass. Pathology anatomy report revealed 10 cancer cases, 1,1% from 950 all cases who came to RSOSÂ  from Januari 2007 until December 2010. 4 cases are insitu carcinoma, 1 nipple discharge with palpable mass, tumor was found 6x6x4 cm. There were 5 cases non cancer, 4 cases intraductal papilloma and 1 periductitis.